Isopropoxy‐Carvacrol, a Derivative Obtained from Carvacrol, Reduces Acute Inflammation and Nociception in Rodents. (19th March 2014) - Bonfim, Rangel R.; Paiva‐Souza, Igor O.; Moraes, Janaína P.; Pereira, Denyson S.; Santos, Cliomar A.; Santana, Danielle G.; Thomazzi, Sara M.; Ferro, Jamile N. S.; Barreto, Emiliano O.; Sousa, Damião P.; Camargo, Enilton A.
Abstract Monoterpenes, compounds mainly presented in essential oils, have important pharmacological actions. Isopropoxy‐carvacrol (IPC) is a derivative of the monoterpene carvacrol, and its pharmacological properties have not yet been investigated. The aim of this study was to analyse the acute anti‐inflammatory and antinociceptive properties of IPC. Mice (25–30 g) and rats (150–230 g) were pre‐treated (i.p.) with IPC at the doses of 10, 30 or 100 mg/kg or vehicle (Tween 80, 0.5%), 30 min. before injection of the phlogistic agents. Both the first and the second phases of formalin‐induced nociception were significantly reduced by IPC (100 mg/kg). Injection of carrageenan in mice paw reduced the threshold of stimulus intensity, applied with an analgesymeter, necessary to cause paw withdrawal, which was significantly reduced by 100 mg/kg of IPC. The area under curve (0–4 hr) of rat paw oedema induced by injection of carrageenan was also significantly diminished by the administration of IPC (100 mg/kg). Administration of 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA) markedly increased mice ear oedema and myeloperidase (MPO) activity. Topical co‐administration of IPC (0.3–3 mg/ear) during the induction did not affect TPA‐induced ear oedema, but significantly decreased MPO activity in the ears, when compared with the vehicle. In in vitro experiments, IPC reduced lipoperoxidation induced by different stimuli, showed nitric oxide scavenger activity and did not interfere with murine macrophage viability in concentrations up to 100 μg/mL. These results demonstrate that IPC exerts acute anti‐inflammatory and antinociceptive activities, suggesting that it may represent an alternative in the development of new future therapeutic strategies.